(untitled) (Proceedings of Southern Federal University. Philology, 2025)
https://doi.org/10.18522/1995-0640-2025-3-117-125 In 2006, Sergei Sergeyevich Kozlov published the novellas “The Boy Without a Sword” and “Bekar,” both featuring adolescents as their protagonists. Set at the turn of the 20th and 21st centuries, the narratives center on issues of social destabilization and emotional breakdown stemming from the dissolution of the Soviet Union. Both works are focused on the comprehension of the ideological crisis, the revival of religious consciousness, and the spiritual transformation of the characters following the USSR’s collapse, allowing for their examination within the framework of contemporary spiritual prose. Focusing on the young generation of Russia as the primary subject of representation, the author masterfully places them at the heart of the narrative structure, demonstrating refined narrative skills, empathy, and a deep understanding of the world and human nature. An analysis of the social and spiritual maturation of the main characters reveals the writer’s reflections on the current state of Russia and its future prospects. Despite facing external and internal crises, the protagonists remain true to their ideals, reflecting their directional thinking and capacity for spiritual evolution. Key words: Sergei Kozlov, “The Boy Without a Sword”, “Bekar”, modern spiritual prose, theme of growth